Facile synthesis of nanocrystalline TiO2 mesoporous microspheres for lithium-ion batteries - Wang, J.; Zhou, Y.; Hu, Y.; O'hayre, R.; Shao, Zongping (2011)
TiO2 mesoporous nanocrystalline microspheres assembled from uniform nanoparticles were synthesized by a facile and template-free hydrolytic precipitation route in normal solvent media. The phase structure, morphology, and pore nature were analyzed by X-ray diffraction, transmission electron microscopy, field-emission scanning electron microscopy, and BET measurements. The electrochemical properties were investigated by cyclic voltammetry, constant current discharge-charge tests, and electrochemical impedance techniques. Microspheres with diameters ranging from 0.2 to 1.0 µm were assembled by aggregation of nanosized TiO2 crystallites (~8-15 nm) and yielded a typical type-IV BET isotherm curve with a surface area of ~116.9 m 2 g-1 and a pore size of ~5.4 nm. A simplified model was proposed to demonstrate the nanoparticle packing modes to form the mesoporous structure. The initial discharge capacity reached 265 mAh g -1 at a rate of 0.06 C and 234 mAh g-1 at a rate of 0.12 C. The samples demonstrated high rate capacity of 175 mAh g-1 at 0.6 C and 151 mAh g-1 at 1.2 C even after 50 cycles, and the Coulombic efficiency was approximately 99%, indicating excellent cycling stability and reversibility. Details of the kinetic process of the nanocrystalline mesoporous microspheres electrode reaction from electrochemical impedance spectra provided further insights into the possible mechanisms responsible for the good reversibility and stability. These investigations indicate that TiO2 nanocrystalline mesoporous microspheres might be a promising anode material for high-energy density lithium-ion batteries.